Review paperBone metabolism disorders and glucocorticoid therapy in patients with pemphigus - Karlińska, Marlena; Waszczykowska, Elżbieta; Torzecka, Jolanta Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Glucocorticoids are the most common cause of secondary osteoporosis, defined as a chronic, progressive disorder characterized by low bone mass and microarchitectural deterioration of bone tissue. The consequence is impairment of bone endurance and increased susceptibility to fracture. It is estimated that 30% to 50% of patients experience vertebral or hip fractures. The highest risk of reduction in bone density is observed in the first 3-6 months of treatment. Glucocorticoids in association with immunosuppressive drugs are still the main method of pemphigus therapy. Most patients undergoing chronic glucocorticoid treatment do not receive optimal osteoporosis diagnosis, prevention and/or treatment.